Expression profile and prognostic relevance of immune infiltration-related RBMS1 in gliomas: a multidimensional integrative analysis - Yang Zhang; Ying Zhou; Sunfu Zhang; Liangxue Zhou (Journal of Cancer Research and Clinical Oncology)
Abstract Purpose This study investigates the expression characteristics of RNA binding motif single stranded interacting protein 1 (RBMS1) in gliomas and its associations with clinicopathological features, immune infiltration, and prognosis, aiming to evaluate its potential as a prognostic biomarker. Methods Differentially expressed genes (DEGs) were screened from the GEO datasets GSE43378 and GSE178621 (thresholds: P < 0.05,|logFC|> 1), with RBMS1 validated via the TCGA and GEPIA databases. Correlations between RBMS1 and immune infiltration were assessed using the TISIDB. Correlations between RBMS1 and immune checkpoint molecules, costimulatory genes, and chemokines were also explored using GEPIA. Immunohistochemistry (IHC) was performed on 165 glioma and 62 normal brain tissues to analyze RBMS1 expression and its clinicopathological relevance (WHO grade, distant metastasis). Three-year survival outcomes were evaluated using Kaplan–Meier (K-M) curves and log-rank tests for overall survival (OS) and relapse-free survival (RFS). Additionally, univariate and multivariate Cox regression analyses were conducted to assess independent prognostic factors. Results Integrated bioinformatic analysis identified RBMS1 as a key DEG, showing significant upregulation in gliomas (TCGA and GEPIA: P < 0.05) and moderate positive correlations with immune cell infiltration (Tregs: r = 0.461; NKTs: r = 0.505; Th1: r = 0.451; all P < 0.001). RBMS1 also showed significant positive correlations with key immune checkpoint molecules (PDCD1, CD274, CTLA4, etc.), costimulatory genes (CD28, TNFRSF9), and chemokines (CXCL9, CXCL10, CCL5), suggesting its potential role in modulating the immune microenvironment. Clinically, RBMS1 positivity was markedly higher in gliomas than controls (59.39% vs. 16.13%, χ2 = 33.822, P < 0.001), correlating with advanced WHO grades (P < 0.001) and distant metastasis (30.62% vs. 14.93%, P = 0.021). Univariate analysis revealed that RBMS1 expression, WHO grade, tumor location, extent of resection, and metastasis were associated with prognosis. Survival analysis revealed significantly worse 3-year OS (34.69% vs. 70.15%) and RFS in RBMS1-positive patients (both P < 0.001). Cox regression analysis confirmed that RBMS1 was an independent prognostic factor for OS (P = 0.028, HR = 1.845, 95% CI: 1.068–3.188), along with WHO grade and metastasis. Conclusion RBMS1 is aberrantly overexpressed in gliomas, associated with tumor aggressiveness, immunosuppressive microenvironment remodeling, and poor prognosis, positioning it as a promising prognostic biomarker and therapeutic target.